Alexandre de Gusmão, o Brasil e o Tratado de Madrid (1735-1750) - Miranda, Tiago Costa Pinto dos Reis (Revista de História, 1991)
ALMEIDA, Luis Ferrand de. Alexandre de Gusmão, o Brasil e o Tratado de Madrid (1735-1750)